Game Pembelajaran Pengenalan Huruf Untuk Anak Inklusi (Autis) Sekolah Dasar - Ninin Mareta; Anang Kukuh Adisusilo; Nia Saurina (Melek IT : Information Technology Journal, 2017)
Elementary school is learning for children up to 7 years old, learning for knowledge development, attitude, and creativity for them. But, not all children be able with well developed. Usually children with difficult developed lean hard to understand about learning. This children’s entered into inclusion class for getting more intensive knowledge development. Mostly, this inclusion children (autism) is who hard to read. The learning method for teaching inclusion children (autism) who hard to reading is game. That game is mixed with the lesson in order to inclusion children can get well lesson. With the game method, they will understand the lesson easier. But, classic game learns bored and not focus. This data got from study literatur, journal, book, and interview this game 3D design game use unity. In this research will make an application learning game to make the inclusion of children (autism) to focus more on the letters introduced. The trial application results for SDN Benowo 3 Surabaya is more than 80% student’s (autism) more interesting use this application.